Penanggulangan COVID-19 dengan Mengadakan Pelatihan Pembuatan Masker kepada Peserta Didik SMKN 3 Palangka Raya - Endang Sri Suyati; Hendri Hendri; Achmad Zainul Rozikin; Gusti Iqbal Tawaqal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Coronavirus Disease 2019 (COVID-19) is a horrendous deadly virus at the end of 2019 and early 2020. This virus attacks all ages and groups indiscriminately, such as adolescents, parents, young children, students, business people, institutions, etc. COVID-19 physically attacks a person and attacks the economy of a person, company, and country. A person who lacks skills will have difficulty surviving this pandemic. So it is necessary to hold training from various agencies, such as the government and universities. The Community Service Team of Universitas Muhammadiyah Palangkaraya held training for students of SMKN 3 Palangkaraya majoring in Fashion Design. This training guides students in producing masks that are environmentally friendly and how to market them effectively and efficiently. Since teaching and learning activities have been disrupted since the arrival of COVID-19, training in producing masks and distributing materials on environmentally friendly literacy, marketing, and learning has been carried out online using the Zoom application. The tutorial was demonstrated by professional tailors and recorded directly by the team, then distributed to SMKN 3 Palangkaraya. The student produces masks with a guide or guidance, according to the video. After finishing production, they get material contains reasons for using splash cloth, protecting the environment, and market the product effectively and efficiently.